Ocalić Gaudium et spes. Nowy humanizm Jana Pawła II - WEIGEL, George; CHABRAJSKA, Dorota (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2012)
The author first sketches the political context of the Second Vatican Council by pointing that its opening coincided with the high point of the Cold War (the Cuban Missile Crisis) and that the political situation of the world was undoubtedly one motive behind John XXIII’s April 1963 encyclical on the imperative of peace, Pacem in Terris. The article is then focused on the contents of Gaudium et Spes, the Pastoral Constitution on the Church in the modern world, the document in the drafting of which Karol Wojtyła played a significant role and which was promulgated at the end of the Council’s fourth period. The author observes that despite the intention of the authors of Gaudium et Spes to address the main challenges of the modern world, today the constitution might seem dated. While its worthy insights include the sympathetic treatment of the contemporary human quest for freedom; the dialogical approach to the challenge of modern atheism; the celebration of the genuine achievements of science and democracy; the ecclesiology of a Church that proposes, but does not impose; the touching description of conscience as “the most secret core and sanctuary of man ... [where] he is alone with God, Whose voice echoes in its depths” (§16), one may, from the perspective of today, point to cultural, social and political phenomena constitutive of the post-modern world which were not anticipated in the document. Identifying these “missing pieces” (such as the implications of the new genetics; displacing the hard sciences by biology and other life sciences as the source of Promethean threats to the human future and to man’s self-understanding; the serious philosophical challenges to Christianity, such as utilitarianism; radical forms of secularism; the “dictatorship of relativism;” the advent of the new feminism and new models of family or the global plague of abortion) is helpful in defining the essence of the challenge of post-modernity. The author holds that despite the apparently outdated character of Gaudium et spes, the new humanism it proposes, resting on Wojtyła’s insight that “the anthropological question is fundamental,” turns out the key to addressing the new social, cultural and economic phenomena. The special aspects of this humanism involve the concept of freedom conceived of as the “freedom for excellence”: freedom as a matter of freely choosing what we can know to be good, and doing so as a matter of moral habit, as well as the basic moral law, which Wojtyła called “the law of the gift.” Both these themes were subsequently developed in the magisterial documents promulgated during the pontificate of John Paul II and they need to be applied in the approach to the key issues today’s world must face. Summarized by Dorota Chabrajska